The crucible : a play in four acts - Miller, Arthur, 1915-2005; Bigsby, C. W. E. ([USA] : Penguin Books, 1995)
A play based on the Salem witchcraft trials of 1692. It deals particularly with the hounding to death of the nonconformist John Proctor.
Introduction by Christopher Bigsby -- A note on the accuracy of this play -- Act one -- Act two -- Act three -- Act four -- Echoes down the corridor -- Cast -- Appendix.
Keywords: Witchcraft -- Massachusetts -- Salem -- Drama